English as a global language - Crystal, David (Cambridge University, 2013)
Language expert David Crystal presents a lively and factual account of the rise of English as a global language and explores the whys and wherefores of the history, current status and future potential of English as the international language of communication. He avoids taking sides and tells the story in a measured but engaging way, backed by facts and figures. This is a book for anyone of any nationality concerned with English: teachers, students, language professionals, politicians, general readers and anyone with a love of the language.